2019
DOI: 10.1111/aab.12502
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal activity of mixtures ofBacillus thuringiensiscrystals with plant oils ofSinapis albaandAzadirachta indica

Abstract: The main purpose of this study was to determine the insecticidal activity of mixtures of Bacillus thuringiensis crystalline toxins and plant substances that could contribute to create a new bioinsecticide of high efficiency. We decided to determine the toxicity of crystals of B. thuringiensis MPU B9 isolate, azadirachtin (NeemAzal), mustard oil and their mixtures against lepidopteran pests: Cydia pomonella, Spodoptera exigua and Dendrolimus pini. The interaction of the components in mixtures against insects wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The use of azadirachtin in synergy with B. thuringiensis (Bandyopadhyay et al, 2014) and karanj (Pongamia pinnata Pierre) was also reported . Azadirachtin was found to enhance the efficacy of B. thuringiensis in Cydia pomonella, S. exigua, and Dendrolimus pini (Konecka et al, 2019). This synergistic effect was observed between azadirachtin and multicapsid nucleopolyhedrovirus (SfMNPV) on the mortality of S. frugiperda (Pineda et al, 2014).…”
Section: Future Directionsmentioning
confidence: 92%
“…The use of azadirachtin in synergy with B. thuringiensis (Bandyopadhyay et al, 2014) and karanj (Pongamia pinnata Pierre) was also reported . Azadirachtin was found to enhance the efficacy of B. thuringiensis in Cydia pomonella, S. exigua, and Dendrolimus pini (Konecka et al, 2019). This synergistic effect was observed between azadirachtin and multicapsid nucleopolyhedrovirus (SfMNPV) on the mortality of S. frugiperda (Pineda et al, 2014).…”
Section: Future Directionsmentioning
confidence: 92%
“…The synergistic effects of neem products on Btk were proved by many research (Togbe et al 2014;Konecka et al 2019). The LC 50 of Bt and azadirachtin (Singh et al 2007) and LC 20 of azadirachtin 0.09% EC (6.99 μg a.i./ mL) and Bt 12.74% EC (51.62 μg a.i./mL) (Abedi et al 2014) caused 100 and 56.7% mortality of H. armigera, respectively, showing a high level of synergism.…”
Section: Synergism Between Botanicals and Entomopathogenic Bacteriamentioning
confidence: 93%
“…In the nine different combinations of rumex extract with Bt strain BLB 250 (30 mg/g of diet), when tested against S. litura larva, seven of them showed synergism causing 100% mortality. Mustard oil can also be used along with Bt crystals for achieving the synergism against Dendrolimus pini, which resulted in twofolds higher mortality (Konecka et al 2019). Recently, carvacrol, a monoterpenoid phenol, extracted from aromatic plants (oregano) also shown synergistic effects with Bt against Cydia pomonella when mixed in the ratio of 1:25,000 and 1:50,000 (Bt: carvacrol) causing 1.5 and 1.9 times higher mortality, respectively.…”
Section: Synergism Between Botanicals and Entomopathogenic Bacteriamentioning
confidence: 99%
“…The isolation procedure was described previously (Konecka et al 2012(Konecka et al , 2015(Konecka et al , 2019. The strains were cultured on a medium for bacteria sporulation (Lecadet and Dedonder 1971) at 308C for seven days.…”
Section: Isolation Of B Thuringiensis Crystalline Proteinsmentioning
confidence: 99%
“…Almost 90% of commercial microbial insecticides are based on a spore-crystals mixture of Bacillus thuringiensis (Damalas and Koutroubas 2018). Plant products are also recommended as efficient biopreparations against insect pests (Konecka et al 2018b(Konecka et al , 2019Mossa 2016). Moreover, recent trends in crop protections involve the use of insecticide mixtures (Sharifzadeh et al 2018).…”
Section: Introductionmentioning
confidence: 99%